Evaluation of remote ischaemic post-conditioning in a pig model of cardiac arrest: A pilot study. (August 2015) - Albrecht, Martin; Meybohm, Patrick; Broch, Ole; Zitta, Karina; Hein, Marc; Gräsner, Jan-Thorsten; Renner, Jochen; Bein, Berthold; Gruenewald, Matthias
Abstract: Background: Remote ischaemic post-conditioning (RIPoC) in which transient episodes of ischaemia (e.g. by inflation and deflation of a blood pressure cuff) are applied after a prolonged ischaemia/reperfusion injury, may have the potential to improve patient outcome and survival following cardiac arrest. In this study we employed a pig model of cardiac arrest and successful cardiopulmonary resuscitation to evaluate the effects of RIPoC on haemodynamics, cardiac tissue damage and neurologic deficit. Materials and methods: A total of 22 pigs were subjected to ventricular fibrillation, cardiopulmonary resuscitation and randomly assigned to Control or RIPoC treatment consisting of 4 cycles of 5 min femoral artery occlusion followed by 5 min of reperfusion starting 10 min after return of spontaneous circulation (ROSC). Post-resuscitation was evaluated by haemodynamics using left ventricular conductance catheters, quantification of cardiac troponin T (cTnT), lactate dehydrogenase (LDH) and creatine kinase (CK). Neurological testing was performed 24 h after return of spontaneous circulation (ROSC). Results: RIPoC resulted in a statistically significant reduction of serum cTnT levels 4 h after ROSC ( P  ≤ 0.01). LDH and CK concentrations were significantly lower in RIPoC treated pigs 24 h after ROSC ( P  ≤ 0.001), suggesting tissue and/or cardioprotective effects of RIPoC. End-systolic pressure volume relationship was significantly increased in RIPoC treated animals 4 h after ROSC ( P  ≤ 0.05). Neurological testing revealed a trend towards an improved outcome in RIPoC treated animals. Conclusions: We propose that RIPoC applied immediately after ROSC reduces serum concentrations of markers for cell damage and improves end-systolic pressure volume relationship 4 h after ROSC.